Prostate cancer radiation therapy: A physician's perspective. Issue 3 (March 2016) - Dal Pra, Alan; Souhami, Luis
Highlights: Radiotherapy is an important therapeutic option in prostate cancer. Higher doses of radiotherapy have an impact on PSA control. Hypofractionated radiotherapy is becoming an attractive treatment option. New technological developments made radiotherapy safer. Abstract: Prostate cancer is the second most common cancer in men and a major cause of cancer deaths worldwide. Ionizing radiation has played a substantial role in the curative treatment of this disease. The historical evolution of radiotherapy techniques through 3D-conformal radiotherapy (3D-CRT), intensity-modulated radiotherapy (IMRT), and image-guided radiotherapy (IGRT) has allowed more accurate and precise treatments toward significant improvements in the therapeutic ratio. The addition of androgen deprivation therapy has significantly improved overall survival becoming the standard therapy for intermediate- and high-risk disease. Many randomized controlled trials have shown improved local control with dose escalation, and hypofractionated RT has been consolidated with proven efficacy and safe clinical results. However, several questions remain open in the radiotherapeutic management of prostate cancer patients and hopefully ongoing studies will shed light on these uncertainties. More individualized approaches are essential through better prognostic and novel predictive biomarkers of prostate radiotherapy response. Clinicians should critically interpret the evolving technologies in prostate cancer radiotherapy with important optimism but balancing the costs and the actual magnitude of clinical benefit. This article provides an overview of the basic aspects of radiotherapy treatment in localized prostate cancer from a physician's perspective.